Sucker - Hornsby, Daniel (Anchor Books, a division of Penguin Random House LLC, 2023)
"Bad Blood meets Succession in this sharp-toothed satire of Silicon Valley and the 1 percent, in which the black-sheep son of an industrial tycoon starts working for a tech pioneer who's running a biomedical startup that promises nothing less than immortality, only to uncover the horrifying truth at the heart of her sublime promises. Chuck Gross would like nothing more than to prune himself from his family tree. He's already clipped his name: trimmed Charles Grossheart, Jr.-son of a notorious labor exploiter, weapons manufacturer, and climate change denier-down to ordinary good-guy Chuck, the "self-made" proprietor of an up-and-coming punk label. But when Daddy threatens to cut him off, Chuck is forced to get a "real job"-and conveniently, an old college friend has just swept back into his life with the perfect opportunity. Famed Harvard dropout and biotech darling Olivia Watt says she is on the verge of totally reinventing the field of medicine-but when Chuck signs on, he soon discovers that things at the vast Kenosis campus are not quite how they appear. Incidents involving secret labs, mutated test subjects, and vanished employees seem to be as impossible as they are sinister. Is Olivia simply a scammer-or does her technology threaten to usher humanity toward a far bloodier fate? Moreover, does Chuck-who has notably never accomplished anything on his own-stand a chance of stopping her? Hornsby hilariously skewers the insatiable hungers of the ultrarich in a novel that no one will be able to resist sinking their teeth into"--